Describing teacher conceptions of technology in authentic science inquiry using technological pedagogical content knowledge as a lens. Issue 4 (9th April 2019) - Mishra, Chandrani; Ha, Soo Jung; Parker, Loran Carleton; L. Clase, Kari
Abstract: Technology has become an indispensable component of both modern life science and life science education. However, due to inadequate knowledge and experience, teachers are often unable to include technology essential for practicing science in their teaching. In this regard, professional development workshops for in‐service and preservice teachers are beneficial. In this study, we described the role of a professional development workshop in enhancing teachers' technological, pedagogical, and content knowledge through the lens of Technological Pedagogical Content Knowledge framework. Our study is also an example of how teachers can be informed about the current trends in modern research and technology and trained to bring similar research into their classroom. © 2019 International Union of Biochemistry and Molecular Biology, 47(4):380–387, 2019.